Reciprocity and gift exchange in markets for credence goods - Serhiy Kandul; Bruno Lanz; Evert Reins (University of Neuchâtel, Institute of Economic Research (IRENE), 2020)
We study the role of reciprocity in markets where expert-sellers have more information about the severity of a problem faced by a consumer. We employ a standard experimental credence goods market to introduce the possibility for consumers to gift the expert-seller before the diagnostic, where the gift is either transferred unconditionally or conditionally on solving the problem. We find that both types of gift reduce undertreatment, whereas unconditional gifts also reduce overcharging and increase undercharging, suggesting that unconditional gifts are perceived as more kind. For high-severity consumers gifting reduces market inefficiencies, although the presence of low-severity consumers mitigates overall efficiency gains.
Keywords: C91; D18; D82; 330; Credence Goods; Gift Exchange; Asymmetric Information; Lab Experiment